Penerapan Algoritma ID3 Decision Tree Pada Klasifikasi Penyakit Diabetes - Hana, Fida Maisa (Universitas PGRI Yogyakarta, 2023)
A Blood glucose levels that exceed normal are a sign of diabetes mellitus (DM), a complex and chronic condition that requires ongoing medical care to reduce the risk of complications through glycemic control. In 2015, there are 10 million people in Indonesia who suffer from diabetes. The number of diabetics is increasing every year. The International Diabetes Federation estimates that the number of people in Indonesia who suffer from diabetes will increase to 16.2 million in 2040. To reduce the risk of complications in the future, diabetes must be detected early. One method that can be used to predict diabetes is the ID3 Decision Tree algorithm. The ID3 algorithm is an algorithm used to form a decision tree. From the test results, it produces a fairly large accuracy of 98.08% with a Precision of 96.88% and a Recall of 100%.